2017
DOI: 10.1007/s11010-017-3023-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 inhibits rat vascular smooth muscle cell calcification by restoring the Gas6/Axl/Akt anti-apoptotic pathway

Abstract: Vascular calcification is associated with cardiovascular disease as a complication of hypertension, hyperlipidemia, diabetes mellitus, and chronic kidney disease. Vitamin K2 (VK2) delays vascular calcification by an unclear mechanism. Moreover, apoptosis modulates vascular smooth muscle cell (VSMC) calcification. This paper aimed to study VK2-modified VSMC calcification and survival cell signaling mediated by growth arrest-specific gene 6 (Gas6) and its tyrosine kinase receptor Axl. Primary-cultured VSMCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…In response to phosphate, a multitude of up-stream signaling cascades may lead eventually also to the activation of pro-apoptotic signaling pathways in VSMCs [ 6 , 56 , 74 , 178 , 182 , 183 ]. A key event is represented by the downregulation of growth arrest-specific gene 6 (Gas6) and its receptor tyrosine kinase Axl [ 74 , 182 , 183 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to phosphate, a multitude of up-stream signaling cascades may lead eventually also to the activation of pro-apoptotic signaling pathways in VSMCs [ 6 , 56 , 74 , 178 , 182 , 183 ]. A key event is represented by the downregulation of growth arrest-specific gene 6 (Gas6) and its receptor tyrosine kinase Axl [ 74 , 182 , 183 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
“…In response to phosphate, a multitude of up-stream signaling cascades may lead eventually also to the activation of pro-apoptotic signaling pathways in VSMCs [ 6 , 56 , 74 , 178 , 182 , 183 ]. A key event is represented by the downregulation of growth arrest-specific gene 6 (Gas6) and its receptor tyrosine kinase Axl [ 74 , 182 , 183 ]. Phosphate reduces the expression of Gas6 and Axl in VSMCs [ 184 ], leading to Bcl2 inactivation, activation of the pro-apoptotic protein Bcl2-associated death promoter (Bad), and subsequent caspase-3 activation and VSMC apoptosis [ 74 , 182 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between Gas6 and Axl activates the PI3K/Akt pathway resulting in stimulation of cell survival pathway [64]. Therefore, apoptosis-mediated VSMC calcification can be inhibited by the Gas6/Axl-PI3K/Akt pathway activated by statin and vitamin K2 [65,66]. GRP also function as an inhibitor of vascular calcification.…”
Section: Matrix Gla Protein and Other Vkdps In Vascular Calcificationmentioning
confidence: 99%
“…Since β-GP can induce apoptosis in HASMCs (Qiu et al, 2017), to examine the downstream apoptotic signaling during β-GP-induced apoptosis in HASMCs, we examined the cleaved form of Caspase3 and Caspase9, Bak, and Bax of which the apoptosis-related protein, and Bcl-2, an inhibitory protein for apoptosis. Results indicated that bavachin dose-dependently suppressed the β-GP-induced expression of apoptosis-related proteins Bax, Bak, Caspase3 and Caspase9, it also prevented the β-GP-mediated suppression of Bcl-2, and the ratio of Bcl-2/Bax was gradually increased ( Figure 4A, p < 0.01).…”
Section: Bavachin Prevents β-Gp-induced Apoptosis In Hasmcsmentioning
confidence: 99%